2019
DOI: 10.1213/ane.0000000000003652
|View full text |Cite
|
Sign up to set email alerts
|

Ability of a New Smartphone Pulse Pressure Variation and Cardiac Output Application to Predict Fluid Responsiveness in Patients Undergoing Cardiac Surgery

Abstract: In patients undergoing cardiac surgery, PPVCAP and PPVPC both weakly predict fluid responsiveness. However, COCAP is not a good substitute for COTD and cannot be used to assess fluid responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Additional validation studies showed that Capstesia had a percentage of error of 20% for PPV and 13.8% for CO among 20 patients in the intensive care unit [ 7 ]. However, when the app was studied in 57 patients undergoing elective cardiac surgeries, its calculated PPV only weakly predicted fluid responsiveness (sensitivity of 73%, 95% CI 0.54-0.92, and a specificity of 74%, 95% CI 0.48-0.90) [ 11 ]. When comparing Capstesia’s PPV to stroke volume variation from an uncalibrated pulse wave analysis monitor, Joosten et al found that there was 79% overall agreement between the two, with a kappa coefficient of 0.55 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional validation studies showed that Capstesia had a percentage of error of 20% for PPV and 13.8% for CO among 20 patients in the intensive care unit [ 7 ]. However, when the app was studied in 57 patients undergoing elective cardiac surgeries, its calculated PPV only weakly predicted fluid responsiveness (sensitivity of 73%, 95% CI 0.54-0.92, and a specificity of 74%, 95% CI 0.48-0.90) [ 11 ]. When comparing Capstesia’s PPV to stroke volume variation from an uncalibrated pulse wave analysis monitor, Joosten et al found that there was 79% overall agreement between the two, with a kappa coefficient of 0.55 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the percentage error in our analysis exceeded the threshold for clinical interchangeability of 30% [ 20 ]. In another validation study, CO PWAsnap was compared to CO measured with transpulmonary thermodilution, a clinical reference method [ 22 , 23 ], in 57 patients during cardiac surgery [ 11 ]. With a mean of the differences between CO measurements obtained by the two methods of 0.3 L min − 1 , wide 95%-LOA of 3.3 to -2.8 L min − 1 , a high percentage error of 60%, and a poor concordance rate the results of this study are consistent with our findings [11].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that close to 10% of the snapshots of the arterial blood pressure waveform cannot be analyzed by PWAsnap [ 11 ]. We did not systematically analyze the quality of the snapshots or the failure rate of PWAsnap to estimate PPV and CO. We thus can only subjectively describe our experiences of using PWAsnap in a clinical setting in the operating room.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations